Spatial impacts of insecurity and economic growth on FDI in Mexico, 1999-2019 - Andrés-Rosales, Roldán; de Jesús Almonte, Leobardo; Cruz Marcelo, José Nabor (Economía Sociedad y Territorio, 2023)
Foreign Direct Investment in Mexico has been of relevance in determining economic growth in Mexican states. Despite being positive for the country, FDI has been limited by prevailing insecurity in different states, which had historically attracted this kind of investment. States in the northern border and in the center have usually attracted the greatest amount of FDI. Through SpVAR we quantified investment and insecurity spillovers in each state and its neighboring states, and we show that the push-in effect has been larger than the push-out effect in Mexico.